A CIPP Model Evaluation of Philanthropy-Based Non-Formal Education: Evidence from a Community Learning Center in Indonesia - Biardini Biardini; Dafid Slamet Setiana (Papanda Publisher, 2026)
Educational disparities persist among pre-prosperous communities in Indonesia, with 2.54 million adolescents lacking formal education access. This study evaluates philanthropy-based educational services at PKBM Binar to assess their effectiveness in enhancing educational access, quality, and program sustainability. Employing Stufflebeam's CIPP (Context, Input, Process, Product) evaluation model with a convergent mixed-methods design, data were collected from 68 participants across five stakeholder groups through questionnaires (Cronbach's α: 0.78-0.92), semi-structured interviews, observations, and document analysis over three months (September-November 2024). Quantitative findings revealed consistently high stakeholder satisfaction across all CIPP dimensions (mean scores: 4.50-4.68/5.0). Qualitative data confirmed program effectiveness in providing accessible, quality education while maintaining sustainability through volunteer educators, donor support, and collaborative governance. Unexpected findings included spontaneous peer mentoring systems and alumni community leadership emergence, suggesting multiplier effects beyond immediate beneficiaries. Results validate philanthropic education's viability in addressing educational inequities. The program successfully operationalizes giving, serving, and associating principles, though challenges in volunteer professional development, post-graduation support, and geographical outreach require strategic attention. Findings extend CIPP model applications while providing actionable insights for similar initiatives.